ANALISIS STRATEGI PENENTUAN LOKASI PEMASARAN DALAM MENINGKATKAN DAYA TARIK PEMBELI PADA UMKM ES DAWET DAN CINCAU DI KOTA MEDAN SUMATERA UTARA - Dea Puspita; Mardiah oktaviani; Muhammad Adhwa Nayatama Sinaga; Zainarti (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to analyze strategies for determining effective marketing locations in attracting buyers for Es Dawet and Cincau MSMEs. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with MSME owners as well as direct observation of the marketing locations used. Data analysis was carried out using content analysis techniques to identify factors that influence buyer attraction. The research results show that accessibility, visibility and presence of target markets are the main factors in determining effective marketing locations. Apart from that, surrounding environmental factors and the presence of competitors also influence buyer attraction. The practical implication of this research is the importance of selecting strategic marketing locations to increase buyer attraction for Es Dawet and Cincau MSMEs. It is hoped that this research can contribute to MSME owners in designing more effective marketing strategies to improve their business performance.